Caracterización del estrés en un adulto mayor de 65 años de edad del Recinto la Maritza - Mosquera Marca, Cristhian Andrés (2023)
The aging of the population is a global trend that has led to an increase in the number of elderly adults facing various health challenges, including stress. This case study focused on a 65-year-old resident of La Maritza community who experiences significant levels of stress in her daily life, exacerbated by issues in her domestic coexistence with her partner and other family members. A psychological intervention was conducted, implementing the use of psychometric tools such as the 1967 Holmes and Rahe Scale. This scale assigns a weighting from 100 to 0 to a specific list of major life events in the past year and, based on these values, determines the presence or absence of the risk of an underlying stress-related illness. In-depth interviews were conducted with the patient to gather information about her subjective experience related to stress. Additionally, data on her physical health and socioeconomic factors were collected. The patient reported experiencing a variety of physical and emotional symptoms related to stress, including irritability, fatigue, anger, and difficulty in relating to her family. She revealed that factors such as conflicts with her partner, illness of a close relative, economic concerns, and being responsible for household cleaning and caregiving significantly contributed to her stress. Her results on stress questionnaires confirmed severe levels of stress. The case study of this elderly woman illustrates the complexity of stress in older adults, with an interaction between emotional, social, and economic factors. It raises a discussion about how crucial it is to address stress in this population. The influence of these factors on the patient's quality of life could be observed. This case study offers an in-depth look at the stress experienced by a 65-year-old elderly adult and emphasizes the importance of considering individual and environmental factors when evaluating and treating stress in older adults. To provide comprehensive care for the health and overall well-being of elderly adults, addressing their stress is fundamental. The findings can be used as a basis for creating efficient intervention strategies and improving the quality of life of older individuals experiencing stress.